CD24-Fc suppression of immune related adverse events in a therapeutic cancer vaccine model of murine neuroblastoma - Wu, Xiaofang; Srinivasan, Priya; Basu, Mousumi; Zimmerman, Talia; Li, Samuel; Wang, Yin; Zheng, Pan; Liu, Yang; Sandler, Anthony David (Frontiers in Immunology, 2023)
The combination of Myc-suppressed whole tumor cells with checkpoint inhibitors targeting CTLA-4 and PD-L1 generates a potent therapeutic cancer vaccine in a mouse neuroblastoma model. As immunotherapies translate from pre-clinical to clinical trials, the potential immune-related adverse events (irAEs) associated with induction of potent immunity must be addressed. The CD24–Siglec 10/G interaction is an innate checkpoint that abrogates inflammatory responses to molecules released by damaged cells, but its role in cancer immunology is not well defined. We investigate irAEs of an effective whole cell neuroblastoma vaccine and subsequently the effect of CD24-Fc, a CD24 and Fc fusion protein, on both the vaccine efficacy and induced irAEs in a mouse neuroblastoma model. We demonstrate that the whole tumor cell vaccine combined with immune checkpoint therapy triggers occult organ specific immune cell infiltrates, primarily in cardiac tissue and to a lesser extent in the renal and lung tissue, but not in the colon. CD24-Fc administration with vaccination partially impedes anti-tumor immunity but delaying CD24-Fc administration after initial vaccination reverses this effect. CD24-Fc treatment also ameliorates the autoimmune response induced by effective tumor vaccination in the heart. This study illustrates that the combination of Myc suppressed whole tumor cell vaccination with checkpoint inhibitors is an effective therapy, but occult immune infiltrates are induced in several organ systems in a mouse neuroblastoma model. The systemic administration of CD24-Fc suppresses autoimmune tissue responses, but appropriate timing of administration is critical for maintaining efficacy of the therapeutic vaccine.